Universityscapes - Žalac, Domen (Družboslovne razprave, 2023)
The purpose of this article is to explore the social and spatial dynamics within the university libraries of the University of Ljubljana and the University of Vienna. The analysis shows that university libraries are crucial for shaping the academic environment and culture and play an important role in city–university relations. Understanding these dynamics is essential for planning and developing university spaces that can effectively respond to the needs and activities of their users. The article applies qualitative research methods and uses interviews with professors, students and assistants along with on-site observations to analyse the dynamics and transformative role of university spaces in Ljubljana and Vienna.
Keywords: Družbeni vidik; knjižnice; mesto; prostorska dinamika; Univerza na Dunaju; Univerza v Ljubljani; univerze; Univerzitetne in visokošolske knjižnice; urbana sociologija